Knowledge, attitude and practice of healthcare ethics among resident doctors and ward nurses from a resource poor setting, Nepal. Issue 1 (December 2016) - Adhikari, Samaj; Paudel, Kumar; Aro, Arja; Adhikari, Tara; Adhikari, Bipin; Mishra, Shiva
Abstract Background Healthcare ethics is neglected in clinical practice in LMICs (Low and Middle Income Countries) such as Nepal. The main objective of this study was to assess the current status of knowledge, attitude and practice of healthcare ethics among resident doctors and ward nurses in a tertiary teaching hospital in Nepal. Methods This was a cross sectional study conducted among resident doctors (n  = 118) and ward nurses (n  = 86) in the largest tertiary care teaching hospital of Nepal during January- February 2016 with a self-administered questionnaire. A Cramer's V value was assessed to ascertain the strength of the differences in the variables between doctors and nurses. Association of variables were determined by Chi square and statistical significance was considered if p value was less than 0.05. Results Our study demonstrated that a significant proportion of the doctors and nurses were unaware of major documents of healthcare ethics: Hippocratic Oath (33 % of doctors and 51 % of nurses were unaware), Nuremberg code (90 % of both groups were unaware) and Helsinki Declaration (85 % of doctors and 88 % of nurses were unaware). A high percentage of respondents said that their major source of information on healthcare ethics were lectures (67.5 % doctors versus 56.6 % nurses), books (62.4 % doctors versus 89.2 % nurses), and journals (59 % doctors versus 89.2 % nurses). Attitude of doctors and nurses were significantly different (p  < 0.05) in 9 out of 22 questions pertaining to different aspects of healthcare ethics. More nurses had agreement than doctors on the tested statements pertaining to different aspects of healthcare ethics except for need of integration of medical ethics in ungraduate curricula (97.4 % doctors versus 81.3 % nurses), paternalistic attitude of doctor was disagreed more by doctors (20.3 % doctors versus 9.3 % nurses). Notably, only few (9.3 % doctors versus 14.0 % nurses) doctors stood in support of physician-assisted dying. Conclusions Significant proportion of doctors and nurses were unaware of three major documents on healthcare ethics which are the core principles in clinical practice. Provided that a high percentage of respondents had motivation for learning medical ethics and asked for inclusion of medical ethics in the curriculum, it is imperative to avail information on medical ethics through subscription of journals and books on ethics in medical libraries in addition to lectures and training at workplace on medical ethics which can significantly improve the current paucity of knowledge on medical ethics.